The Transformational Leadership of Administrator and High Performance Organization in School Under Secondary Educational Service Area Office Suratthani Chumphon - Kamolnate, Warittha; Intarak, Assoc.Prof.Dr.Prasert (Journal of Dhamma for Life, 2024)
The objectives of this research were to determine: 1) transformational leadership of school administrator 2) high performance organization in school 3) the relationship between transformational leadership of school administrator and high performance organization in school. The sample was 59 schools under secondary educational service area office Suratthani Chumphon. The 2 respondents from each school consisted of a school director and a teacher, with the total of 118. The research instrument was a questionnaire regarding transformational leadership of school administrator, based on the concept of Bass and Avolio and high performance organization of school, based on the concept of De Waal. The statistics used for data analysis were frequency, percentage, arithmetic mean, standard deviation, and Pearson’s product-moment correlation coefficient. The research finding revealed that: 1) Transformational leadership of school administrator as a whole and each aspect were at a high level. The arithmetic mean ranking from the highest to the lowest were as follows; individualized consideration, idealized influence, inspiration motivation and intellectual stimulation. 2) High performance organization in school as a whole and each aspect were at a high level. The arithmetic mean ranking from the highest to the lowest were as follows; employee quality, long-term orientation, openness and action orientation, management quality and continuous improvement and renewal. 3) The relationship between transformational leadership of school administrator high performance organization in school were found at high level of .01 statistical significances.